A FlexibleWO(3)-Based pH Sensor Array for 2-D pH Monitoring Using CPLoP Technique - Fu, Yu-Min; Pan, Jia-Chyi; Tsou, Kun-Lin; Cheng, Yu-Ting (My University, 2018)
In this letter, we demonstrate an inkjet-printed WO3-based pH sensor array using WO3/Ag and Ag/AgCl as working and reference electrodes, respectively, on a flexible polyimide substrate. Pre-treated by Tollen's reagent, the printed Ag lines as sensor interconnects can exhibit a denser microstructure with lower electrical resistivity. As a result, the WO3 nanoparticles can be well printed and sintered at 120 degrees C on the Ag lines as the working electrodes of the pH sensors. Experimental results show the sensitivity of the pH sensor to be as high as -24.4 mV/pH. The array comprising six pH sensors shows potential for real-time 2-D pH sensing applications.
Keywords: Flexible pH sensor; WO3; sensor array; inkjet printing